The Role of Fleet Management in Improving Fuel Efficiency, Crew Productivity, and Shipping Company Revenues - Dony Ari Nugroho (Green Publisher Indonesia, 2025)
The shipping sector in Indonesia is growing rapidly, but fierce competition and the dominance of foreign vessels are forcing shipping companies to improve fuel efficiency, crew productivity, and revenue. This study aims to conduct an in-depth analysis of the role of fleet management in improving the operational performance of shipping companies. The approach used is qualitative descriptive, with data collection through literature review and interviews. Data analysis is conducted thematically, starting from data reduction, presentation in narrative form, to drawing conclusions to identify patterns. The results of the study show that the implementation of effective fleet management, including route planning, fuel consumption monitoring, and ship maintenance scheduling, can reduce fuel consumption. Crew productivity increases through systematic assignments, continuous training, and the use of fleet monitoring technology, which has a positive impact on shipping safety and delivery smoothness. This impact is also reflected in increased company revenue through reduced operational costs and improved profit margins. The implications of the research findings highlight the importance of an integrated fleet management strategy to enhance operational efficiency, crew productivity, and the competitiveness of shipping companies such as those in Indonesia